Research on teaching global issues : pedagogy for global citizenship education - Myers, John P. 1968- (Research in social education., 2020)
"This edited book is the first full-length volume exclusively devoted to new research on the challenges and practices of teaching global issues. It addresses the ways that schools can and do address young people's interest and activism in contemporary global issues facing the world. Many young people today are passionate about issues such as climate change, world poverty, and human rights but have few opportunities in schools to study such issues in depth. This book draws on new research to provide a deeper understanding and examples of how global issues are taught in schools. The book is organized in two sections: (1) contexts and policies in which global issues are taught and learned; and (2) case studies of teaching and learning global issues in schools. The central thesis is that global issues are an essential feature of democracy and social action in a world caught in the thrall of globalization. Schools can no longer afford to ignore teaching about issues impacting across the world if they intend to keep young people engaged in learning and want them to make their own communities-and the greater world-better places for all"--